Fast lightweight block cipher design with involution substitution permutation network (SPN) structure - Omar A. Dawood (Institute of Advanced Engineering and Science, 2020)
In the present paper, a new cryptographic lightweight algorithm has been developed for the internet of things (IoT) applications. The submitted cipher designed with the involution Substitution Permutation Network SPN structure. The involution structure means that the same encryption algorithm is used in the decryption process except the ciphering key algorithm is applied in reverse order. The introduced algorithm encrypts the data with a block size of 128-bit 192-bit or 256-bit, which iterative with 10, 12 and 14-rounds respectively similar to the AES cipher. The design aspect supports an elegant structure with a secure involution round transformation. The main round is built without S-Box stage instead that it uses the on-fly immediate computing stage and the involution of mathematical invertible affine equations. The proposed cipher is adopted to work in a restricted environment and with limited resources pertaining to embedded devices. The proposed cipher introduces an accepted security level and reasonable gate equivalent (GE) estimation with fast implementation.